The Commemorative Activities of Francysk Skaryna in Lithuania 1990–2022 - Nijolė Bliūdžiuvienė (Knygotyra, 2023)
Over the centuries, Francysk Skaryna’s name has become an object of collective memory and research. The article explores the commemorative activities of Skaryna in Lithuania. The article is based on the approach of the Activity Theory of the commemorative activities of F. Skaryna, which allows conducting a complex analysis of the research topic. The aim of the article is to analyze the memorialization of Skaryna in terms of the conducted activity, while distinguishing its characteristic elements – goals, objects, entities, processes, means and results, with the main focus on the subjects and the means of the implemented activity. The object of the research is the activity of commemorating and remembrance of the memory of Skaryna in the period dating from 1990 to 2022. The analyzed data includes scientific publications related to the memorialization of F. Skaryna in Lithuania, official documents, internet resources, media reports, and publications on the websites of science and studies, educational and cultural institutions. The memorialization was achieved by means of monumental and symbolic measures. The remembrance measures fostered historical and cultural memory, developed intercultural dialogue, and supported humanistic ideas. Monumental and symbolic measures, scientific and artistic events, educational activities, creative projects, monographs and religious honoring have made it possible to remember and get to know the heterogeneous personality and activities of Francysk Skaryna. Most of the commemorative and remembrance measures have been devoted to the celebration of anniversaries of his life and activities. At the level of entities, the cohesion of scientists, artists, representatives of culture, education, public organizations and national as well as foreign institutions at various levels has been remarkable, which has contributed to the implementation of numerous measures of the memorialization of F. Skaryna denoted by cultural, artistic, scientific, social, and lasting value for the communication of memory. The analysis of Skaryna’s memorialization activities has allowed us to draw up a generalized model which enables us to reveal and understand this activity as a social, cultural and scientific action and phenomenon through the totality of its elements.